2018
DOI: 10.15252/embj.201798588
|View full text |Cite
|
Sign up to set email alerts
|

The MRX complex regulates Exo1 resection activity by altering DNA end structure

Abstract: Homologous recombination is triggered by nucleolytic degradation (resection) of DNA double-strand breaks (DSBs). DSB resection requires the Mre11-Rad50-Xrs2 (MRX) complex, which promotes the activity of Exo1 nuclease through a poorly understood mechanism. Here, we describe the Mre11-R10T mutant variant that accelerates DSB resection compared to wild-type Mre11 by potentiating Exo1-mediated processing. This increased Exo1 resection activity leads to a decreased association of the Ku complex to DSBs and an enhan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 67 publications
(155 reference statements)
1
25
0
Order By: Relevance
“…It has been well demonstrated that EXO1 functions in the end resection and HR pathway of DSB repair in the G2 phase and is associated with its phosphorylation by CDK1/2 [17,18]. Theoretically, the function of EXO1 is stringently restrained in G1 phase, where the HR pathway does not work due to a lack of the homologous DNA template for repair.…”
Section: Ubiquitination-mediated Degradation Of Exo1 Is Selectively Amentioning
confidence: 99%
“…It has been well demonstrated that EXO1 functions in the end resection and HR pathway of DSB repair in the G2 phase and is associated with its phosphorylation by CDK1/2 [17,18]. Theoretically, the function of EXO1 is stringently restrained in G1 phase, where the HR pathway does not work due to a lack of the homologous DNA template for repair.…”
Section: Ubiquitination-mediated Degradation Of Exo1 Is Selectively Amentioning
confidence: 99%
“…This persistent unwinding can account for both the enhanced access to DNA ends and processing activity of Exo1 by Mre11-R10T. In fact, easily melted dsDNA ends facilitate in vitro the resection activity of Exo1 and its stimulation by MRX 9 . Furthermore, substitution with alanine of both arginine 368 and 412 residues, through which the Mre11-R10T capping domain contacts the dsDNA, reduces the ability of Mre11-R10T to promote Exo1-mediated DSB resection 9 , indicating that the increased Exo1 activity depends on the interaction between the Mre11 capping domain and the dsDNA.…”
mentioning
confidence: 99%
“…Exo1 is able to degrade the 5ʹ-terminated strand within dsDNA and, therefore, it in principle does not require an helicase activity to unwind the dsDNA 1 . However, our recent characterization of the hypermorphic Saccharomyces cerevisiae Mre11-R10T mutant variant has allowed to demonstrate that the strand-separation function of MRX is important to stimulate Exo1 resection activity 9 . In particular, the mre11-R10T mutation accelerates DSB resection compared to wild type Mre11 by potentiating the processing activity of Exo1, whose association to DSBs is increased in mre11-R10T cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The resulting nick generates an entry site for the Mre11 exonuclease, which degrades back toward the DSB end in the 39-59 direction, and for the long-range resection nucleases Exo1 and Dna2 that degrade away from the DSB in the 59-39 direction (Mimitou and Symington 2008;Zhu et al 2008;Cejka et al 2010;Niu et al 2010;Garcia et al 2011;Nimonkar et al 2011;Shibata et al 2014;Reginato et al 2017;Wang et al 2017). In addition to a nucleolytic activity in the vicinity of the broken DNA ends, MRX has a structural role in recruiting and promoting the activity of Exo1 and Dna2 at DNA DSBs (Cejka et al 2010;Nicolette et al 2010;Niu et al 2010;Shim et al 2010;Cannavo et al 2013;Gobbini et al 2018).…”
mentioning
confidence: 99%